Late permian brachiopoda fauna in north-western iran (2013)
Late Permian marine sequence of in the North west of  Iran in eastern Azarbaijan province in the Zal stratigraphic section has been selected To study brachiopods.Samples have been collected from Alibashi and Jolfa Formation. 27 species of 13 geniuses of brachiopods have been recognized in this study.The comparison of recognized fossil community to brachiopod communities in some regions of Iran and Tethys realm suggests late Dzhulfian as the age of understudy deposits. Recognized prachiopodas belong to Athyride, Rhinconellidae, Productidae and Strophominidae categories